1973
DOI: 10.1128/jb.113.3.1280-1288.1973
|View full text |Cite
|
Sign up to set email alerts
|

Respiration of Bdellovibrio bacteriovorus Strain 109J and Its Energy Substrates for Intraperiplasmic Growth

Abstract: Measurements of oxidation rates, respiratory quotients (RQ), and release of 14 CO 2 from uniformly labeled substrates showed that glutamate, α-ketoglutarate, and synthetic and natural amino acid mixtures are oxidized by suspensions of Bdellovibrio bacteriovorus strain 109J. The oxidation of these substrates largely suppress the endogenous respiration of the Bdellovibrio cells and may or may not cause a small increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 14 publications
3
59
0
Order By: Relevance
“…The exoenzymes responsible for the degradation of substrate cell macromolecules must be released by the bdellovibrio into what was the periplasmic space or the protoplast of the attacked cell or into both and must be retained there. Included among these enzymes would be proteases, known to be produced by the bdellovibrios (11,12,19), which generate the amino acids used for biosynthesis and energy production (17). These could act not only on substrate cell proteins, including the substrate cell's DNases, whose inactivation was discussed above, but also on the other exoenzymes introduced by the bdellovibrio into the bdelloplast chamber.…”
Section: Resultsmentioning
confidence: 99%
“…The exoenzymes responsible for the degradation of substrate cell macromolecules must be released by the bdellovibrio into what was the periplasmic space or the protoplast of the attacked cell or into both and must be retained there. Included among these enzymes would be proteases, known to be produced by the bdellovibrios (11,12,19), which generate the amino acids used for biosynthesis and energy production (17). These could act not only on substrate cell proteins, including the substrate cell's DNases, whose inactivation was discussed above, but also on the other exoenzymes introduced by the bdellovibrio into the bdelloplast chamber.…”
Section: Resultsmentioning
confidence: 99%
“…bacteriovorus is extremely limited. Hespell et al (6) have shown that glutamate is readily oxidized by the obligately predacious B. bacteriovorus strain 109J, and alanine and tryptophan are only slowly oxidized. None of these amino acids is attractive to B. bacteriovorus strain UKi2.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the survival value of chemotaxis for B. bacteriovorus, it would be useful to know what types of compounds are attractive to bdellovibrios. It has previously been shown that these cells can oxidize and incorporate amino acids but do not incorporate carbohydrates (6), and that starvation of bdellovibrios in the absence ofprey is relieved by amino acids (7). Furthermore, some amino acids serve as attractants as well as sources of carbon and energy for potential prey cells such as Escherichia coli (8) and Salmonella typhimurium (3).…”
mentioning
confidence: 99%
“…Bdellovibrio species are ubiquitous aerobic gram-negative bacteria, extremely small, that attack and infect other bacteria by growing in the space between their cell wall and cell membrane (13). The relationship is more accurately that of predator-prey than parasite-host (2). After an often violent, and perhaps chemotactically mediated, collision between rapidly moving bdellovibrios and their targets (15), attachment occurs via several pilus-like filaments (13,15).…”
mentioning
confidence: 99%
“…When gonococci were mixed with more natural target bacilli for individual bdellovibrios, there was rapid attachment and penetration of the gramnegative rods by the bdellovibrios, whereas gonococci (and S. aureus 502A and L. monocytogenes) were ignored. Failure of bdellovibriogonococcal interaction occurred regardless of gonococcal colony morphology (Ti, T2, or T3), piliation (Ti), penicillin susceptibility, or mo- 2 1/0…”
mentioning
confidence: 99%